Re-Industrialization and Innovative Development of Russia - DANILOV, Ivan P.; ILYINA, Ekaterina A.; LADYKOVA, Tatiana I.; MOROZOVA, Nataliia V.; NIKIFOROV, Yuri G. (Journal of Advanced Research in Law and Economics, 2017)
The relevance of the study is caused by the need of developing both the theory and practice of management of the Russian industry production systems’ innovative development that contribute to bridging the existing gap in the levels of technological and socio-economic development of modern Russia and the world leaders, without which it is impossible to keep the state sovereignty of Russia. In this context, the article is aimed at studying and developing innovative activity management mechanisms and methods in the industry through the creation and functioning of innovative infrastructure in the conditions of re-industrialization, which contribute to increasing human capital. The main approach to the study of this problem is the use of methodological concepts of institutional economics, innovation theory, system’s and comparative analyses, structural and functional analysis, allowing to comprehensively consider the issues of innovation and production developing management. The article is presenting an analysis of the state of the innovation activity in today's Russia, the state of the methodology and tools to manage re-industrialization. The article materials can be useful in creating methodology and system’s instruments, appropriate to modern conditions, to perfect the innovation activity through improving innovative infrastructure management.